Leadership For A Successful Quality Journey (Global Journal of Management and Business Research, 2012)
The need for leaders arises for the critical roles that they play in leading people groups, without leadership a group of human beings quickly degenerates into arguments and conflicts, because humans see things in different ways and lean toward different solutions. Leadership is a skill needed to influence others#x2019; thoughts, attitudes and behaviors. Leadership is an important skill not only for people in higher positions, but also for so other people in different organizational levels. Leaders set directions to others and help them to clearly visualize the goals that they are targeting. Moreover, leaders encourage, motivate and inspire others to achieve the desired results.
Keywords: organizational; leaders encourage; motivate and inspire